United Kingdom : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2022)
This Technical Report discusses the results of the Public Investment Management Assessment (PIMA) of the United Kingdom (UK) undertaken in April 2022. The assessment is timely as the UK plans to increase infrastructure investment in order to boost economic growth, reduce regional disparities and help achieve the climate transition. The PIMA finds that the UK is well positioned to implement the planned ramp-up of public investment given it has robust institutions throughout the public investment cycle. Notwithstanding this, the Report suggests areas for reform that could increase efficiency and unlock greater value from public investment. The application of the Climate-PIMA module is covered in a separate companion report.